A pH‐sensitive Macromolecular Prodrug as TLR7/8 Targeting Immune Response Modifier. Issue 70 (4th September 2017) - Aichhorn, Stefan; Linhardt, Anne; Halfmann, Angela; Nadlinger, Markus; Kirchberger, Stefanie; Stadler, Manuela; Dillinger, Barbara; Distel, Martin; Dohnal, Alexander; Teasdale, Ian; Schöfberger, Wolfgang
Abstract: The chemical synthesis and biological activity of novel functionalized imidazoquinoline derivatives (ImQ) to generate Toll‐like receptor (TLR) 7/8 specific prodrugs are presented. In vivo activity of ImQs to induce inflammation was confirmed in zebrafish larvae. After covalent ligation to fully biodegradable polyphosphazenes (ImQ‐polymer), the macromolecular prodrugs were designed to undergo intracellular pH‐sensitive release of ImQs to induce inflammation through binding to endosomal TLR7/8 (danger signal). We showed ImQ dissociation from prodrugs at a pH 5 pointing towards endosomal prodrug degradability. ImQ‐polymers strongly activated ovalbumin‐specific T cells in murine splenocytes as shown by increased proliferation and expression of the IL‐2 receptor (CD25) on CD8+ T cells accompanied by strong IFN‐γ release. ImQ prodrugs presented here are suggested to form the basis of novel nanovaccines, for example, for intravenous or intratumoral cancer immunotherapeutic applications to trigger physiological antitumor immune responses. Abstract : GoPro for T cells : A novel pH‐sensitive polyphosphazene–imidazoquinoline conjugate serves as a TLR7/8 targeting macromolecular prodrug for T cell activation.